A Comparative Computational Investigation on Amantadine Adsorption on the Surfaces of Pristine, C-, Si-, and Ga-doped Aluminum Nitride Nanosheets - Babak Mohammadi; Mohammad Reza Jalali Sarvestani (Journal of Chemistry Letters)
Amantadine is a multipurpose medication that its determination is of great importance. Therefore, in this investigation, the performance of pristine, C-, Si-, and Ga-doped aluminum nitride nanosheets as a sensor for electrochemical detection of AT was evaluated by density functional theory computations. The calculated adsorption energies were -17.22, -19.06, -28.98, and -20.36 kcal/mol in the cases of pristine, Si-, Ga-, and C-doped nanosheets, respectively. Hence, the strongest interaction was observed between AT and Ga-doped aluminum nitride nanosheet. On the other hand, the band gap values of pristine, Si-, Ga-, and C-doped nanosheets experienced -1.81%, -10.59%, -20.74%, -2.53% decrease in the adsorption process of AT indicating when AT adsorbs on the surface of Ga-doped AlN nanosheet the electrical conductivity improved more tangibly in comparison to the other scrutinized nanostructures and this adsorbent can be used as an excellent electrocatalytic modifier for the development of novel electrochemical sensors for the detection of AT.